Molecular Interactions in the Voltage Sensor Controlling Gating Properties of Ca(V) Calcium Channels - Tuluc, Petronel (Structure, 2016)
Voltage-gated calcium channels (Ca(V)) regulate numerous vital functions in nerve and muscle cells. To fulfill their diverse functions, the multiple members of the Ca(V) channel family are activated over a wide range of voltages. Voltage sensing in potassium and sodium channels involves the sequential transition of positively charged amino acids across a ring of residues comprising the charge transfer center. In Ca(V) channels, the precise molecular mechanism underlying voltage sensing remains elusive. Here we combined Rosetta structural modeling with site-directed mutagenesis to identify the molecular mechanism responsible for the specific gating properties of two Ca(V)1.1 splice variants. Our data reveal previously unnoticed interactions of S4 arginines with an aspartate (D1196) outside the charge transfer center of the fourth voltage-sensing domain that are regulated by alternative splicing of the S3-S4 linker. These interactions facilitate the final transition into the activated state and critically determine the voltage sensitivity and current amplitude of these Ca(V) channels.